Evangelical historiography: may a historian legitimately look for God's hand in Church history? - Marinello, Thomas J. (European journal of theology, 2015)
This essay provides a qualified yes to the question of whether an evangelical historian can legitimately look for the hand of Cod in Church history. After noting that God is the master and creator of history, pneumatological reasons for this qualified yes are provided. Limits and cautions are then reviewed. First, the evangelical historian should not approach the interpretation of Church history with a triumphalist attitude. Second, he needs to be aware of how it is his theological and other assumptions may affect his historiography. Third, he should be cognizant that historians from different parts of Christianity (or even different evangelical historians) may indeed see the active hand of God as causing a particular historical outcome, but for very different reasons. Ultimately, while an evangelical historian may see the hand of God in Church history, it likely only will be a glimpse and is subject to a revisit when more data is discovered.